Prevalence of leptospiral antibody in sows in Japan - Kikuchi, N., Rakuno Gakuen Univ., Ebetsu, Hokkaido (Japan); Shikano, M; Hatanaka, M; Takahashi, T; Mori, K; Fujii, T; Furuya, T (Japan society of veterinary epidemiology, 2009)
The prevalence of leptospiral antibodies in sows was investigated throughout Japan using microscopic agglutination test (MAT). A total of 1,121 sows raised in 140 farms in 20 prefectures between 2001 and 2004 were randomly selected for serological survey. Sows positive for leptospiral antibodies were found in 98 (70.0%) of the 140 farms. Of the 1,121 sows examined, 281 (25.1%) were positive. The positive rate for serovar Bratislava was the highest and was detected in 202 sows (18.0%) in 87 farms (62.1%), followed by Australis in 84 sows (7.5%) in 45 farms (32.1%), Autumnalis in 25 sows (2.2%) in 25 farms (17.9%), and Canicola in 25 sows (2.2%) in 14 farms (10.0%). The wide prevalence of leptospiral antibody in sows in Japan has been confirmed by MAT in this study, and serovar Bratislava was the major serovar detected.